Effects of concurrent medications on the phenytoin level among adult patients with epilepsy in Hospital Sultanah Nur Zahirah, Terengganu - Zakaria, Nur Izzati Athirah; Mohammad Riza, Nur Qistina (2016)
The effects of concurrent medications on phenytoin level among adult patients with epilepsy have been investigated. This study focused on the consequences of multiple medications intake on the phenytoin level which could result in a positive or negative condition. Our study was carried out at Hospital Sultanah Nur Zahirah, Terengganu which have quite a lot of epilepsy patients. However, not many epileptic patients fulfill our inclusion to become our study subject, therefor resulting in 22 patients. Our study subject had been selectively chosen from the therapeutic drug monitoring (TDM) data form and Hospital Information System (HIS) according to our specifications. The aim of this study is to relate whether consuming other medications together with phenytoin by epilepsy patients affect phenytoin level. This study seems to be important as it can provide us with information on various drug groups that can alter phenytoin’s concentration in the blood if they are taken concurrently. From the 22 patients that we manage to choose, we analyzed them and key in the data into Microsoft Excel Software 2010 to tabularize and also graph them. The result from this study can be used to increase the awareness on the importance of TDM in prescribing the suitable dose of drugs. Hopefully, the efficacy of the drugs can be optimized and thus, increase the patients’ adherence to the drugs.